Management of metastatic renal cell carcinoma patients with poor-risk features: current status and future perspectives. Issue 6 (June 2013) - Santoni, Matteo; De Tursi, Michele; Felici, Alessandra; Lo Re, Giovanni; Ricotta, Riccardo; Ruggeri, Enzo Maria; Sabbatini, Roberto; Santini, Daniele; Vaccaro, Vanja; Milella, Michele
With seven agents approved for renal cell carcinoma within the past few years, there has undoubtedly been progress in treating this disease. However, patients with poor-risk features remain a challenging and difficult-to-treat population, with the mTOR inhibitor, temsirolimus, the only agent approved in the first-line setting. Phase III trial data are still lacking VEGF-pathway inhibitors in patients with poor prognostic features. Poor-risk patients need to be considered as a heterogeneous population. Further understanding of biomarkers can lead to a better selection of patients who may benefit the most from treatment and improvements in prognosis. The presence of poor Karnofsky scores and liver or CNS disease may affect the outcome of these patients much more than other identified factors. This consideration may provide the rationale to further stratify poor-risk patients further subgroups destined to receive either cure or palliation.